Implementasi Penatausahaan Keuangan Desa di Kecamatan Kalasan, Kabupaten Sleman: Evaluasi Praktik Akuntabilitas - Lestyowati, Jamila (Journal Pemberdayaan Masyarakat Indonesia, 2019)
This study aims to analyze the implementation of village financial administration in four villages in Kalasan sub-district, Sleman namely Purwomartani, Selomartani, Tamanmartani, and Tirtomartani. Village financial administration includes recording and administering revenue and expenditure activities carried out by the village treasurer both manually and use financial applications. The research method used a descriptive qualitative approach by taking respondents with purposive sampling. Collecting data was conducted by in-depth interviews, documentation, and observation with the village treasurer and village finance committee. The analytical method used a comparative analysis between villages based on Ministry of Internal Affairs Regulation No. 113 of 2014. The results of this study showed that village financial administration has been carried out through the Village Finance System (Siskeudes) application. Not all administrative activities carried out by village financial managers, some are carried out by village companions. There are several obstacles in the implementation of village financial administration, i.e. human resources, lack of understanding of regulations, lack of supervision and infrastructure facilities.